ChemInform Abstract: Chemoselective Alkylations with N‐ and C‐Metalated Nitriles. Issue 7 (January 2016) - Yang, Xun; Nath, Dinesh; Fleming, Fraser F.
Abstract: The reaction of N‐lithiated cyclohexanecarbonitrile with bifunctional electrophiles or a 1:1 mixture of methyl cyanoformate and benzyl bromide proceeds chemoselectively to afford 1‐alkylated cyclohexanecarbonitriles (III), (VI), and (XI), whilst the reaction of C‐magnesiated nitriles gives rise to 1‐acylated products such as (IV), (VIII), and (XII).